Implementation of marketing and legal tools in the process of commercialization for innovative products in strategic management and entrepreneurship - Аленін, Юрій Павлович; Аленин, Юрий Павлович; Аленін, Ю. П.; Alenin, Yurii P.; Біловодська, Олена Анатоліївна; Біловодська, О. А.; Беловодская, Елена Анатольевна; Bilovodska, Olena A.; Мельник, Юлія Миколаївна; Мельник, Ю. М.; Мельник, Юлия Николаевна; Melnyk, Yuliia M.; et al. (University of Montenegro, 2020)
The subject of the research is the innovative products commercialization process features in strategic management and entrepreneurship marketing and legal aspects. The testing of the used methods and techniques was carried out on the example of the innovative enterprise. The methodical approach of the study is based on the analytic and descriptive approach and is aimed at providing a case study. Thus, the aim of the study is to analyze the marketing and legal component at different stages of the innovative products commercialization process and the adaptation of theoretical and methodological approaches at an empirical level. The study demonstrates which marketing and legal tools and at what stages of commercialization it is advisable to use, and also proves the economic efficiency of the innovative project according to the described methodology. The results of calculations and analysis confirmed the effectiveness of the methodological approaches and enterprise development strategies use.

Предметом дослідження є особливості процесу комерціалізації інноваційних продуктів у стратегічному менеджменті та підприємницькому маркетингу та юридичні аспекти. Тестування використовуваних методів і прийомів проводилось на прикладі інноваційного підприємства. Методичний підхід дослідження базується на аналітичному та описовому підході та спрямований на надання конкретного дослідження. Таким чином, метою дослідження є аналіз маркетингово-правової складової на різних етапах процесу комерціалізації інноваційної продукції та адаптація теоретичного та методологічного підходів на емпіричному рівні. Дослідження демонструє, які маркетингові та правові інструменти та на яких етапах комерціалізації доцільно використовувати, а також доводить економічну ефективність інноваційного проекту за описаною методологією. Результати розрахунків та аналізу підтвердили ефективність методологічних підходів та використання стратегій розвитку підприємства.
Bilovodska O. Implementation of marketing and legal tools in the process of commercialization for innovative products in strategic management and entrepreneurship / О. Bilovodska, Y. Melnyk, Y. Alenin, L. Arkusha // International Journal for Quality Research. – V. 14 (4). – University of Montenegro, 2020. – Р. 1261–1278.
Keywords: Commercialization; Innovation; Marketing tools; Legal tools; Innovative products; Consumer; Strategy; Marketing-mix; Patent; Licensing; комерціалізація; інновації; інструменти маркетингу; правові інструменти; інноваційні продукти; споживач; стратегія; комплекс маркетингу; патент; ліцензування; коммерциализация; инновации; маркетинговые инструменты; правовые инструменты; инновационные продукты; потребитель; стратегия; комплекс маркетинга; патент; лицензирование; Research Subject Categories::SOCIAL SCIENCES::Business and economics; Research Subject Categories::LAW/JURISPRUDENCE::Other law; Предметом исследования являются особенности процесса коммерциализации инновационных продуктов в стратегическом менеджменте и предпринимательском маркетинге и правовые аспекты. Апробация используемых методов и приемов проводилась на примере инновационного предприятия. Методический подход исследования основан на аналитическом и описательном подходе и направлен на предоставление тематического исследования. Таким образом, цель исследования - проанализировать маркетинговую и правовую составляющую на разных этапах процесса коммерциализации инновационной продукции и адаптировать теоретические и методологические подходы на эмпирическом уровне. Исследование демонстрирует, какие маркетинговые и юридические инструменты и на каких этапах коммерциализации целесообразно использовать, а также доказывает экономическую эффективность инновационного проекта по описанной методике. Результаты расчетов и анализа подтвердили эффективность использования методических подходов и стратегий развития предприятия.